Maternal HIV infection and other factors associated with growth outcomes of HIV-uninfected infants in Entebbe, Uganda - Muhangi, Lawrence; Lule, Swaib A.; Mpairwe, Harriet; Ndibazza, Juliet; Kizza, Moses; Nampijja, Margaret; Nakazibwe, Esther; Kihembo, Macklyn; Elliott, Alison M.; Webb, Emily L. (Public health nutrition, 2013)
To assess the associations between maternal HIV infection and growth outcomes of HIV-exposed but uninfected infants and to identify other predictors for poor growth among this population. Within a trial of de-worming during pregnancy, the cohort of offspring was followed from birth. HIV status of the mothers and their children was investigated and growth data for children were obtained at age 1 year. Lengthfor- age, weight-for-age and weight-for-length Z-scores were calculated for each child; Z-scores ,22 were defined as stunting, underweight and wasting, respectively. Setting: The study was conducted in Entebbe municipality and Katabi subcounty, Uganda. Subjects: The sample consisted of 1502 children aged 1 year: HIV-unexposed (n 1380) and HIV-exposed not infected (n 122). Results: Prevalence of stunting, underweight and wasting was 14?2%, 8?0% and3?9%, respectively. There was evidence for an association between maternal HIV infection and odds of being underweight (adjusted OR52?32; 95% CI 1?32, 4?09; P50?006) but no evidence for an association with stunting or with wasting. Young maternal age, low maternal education, low birth weight, early weaning and experiencing a higher number of episodes of malaria during infancy were independent predictors for stunting and underweight. A higher number of living children in the family was associated with wasting. Conclusions: Maternal HIV infection was associated with being underweight in HIV-exposed uninfected infants. The success of programmes for prevention of mother-to-child HIV transmission means that an increasing number of infants will be born to HIV-infected women without acquiring HIV. Therefore, viable nutritional interventions need to be identified for this population.
Keywords: Maternal HIV infection; Growth outcomes; HIV-uninfected infants; Uganda